PERSEPSI PEMANGKU KEPENTINGAN DALAM PENGELOLAAN WISATA BAHARI DI KEPULAUAN KAPOPOSAN KABUPATEN PANGKEP - Khrisna Samudra; Mulyono S. Baskoro; Sugeng Hari Wisudo; Budhi H. Iskandar (Jurnal Teknologi Perikanan dan Kelautan, 2010)
Kapoposan islands in Pangkep Regency consist of six small islands named are Kapoposan, Gondongbali, Papandangan, Suranti, Tambakulu and Pamanggangan. Those six islands with the area, will be developing on marine tourism activities. The primary data was collected by survey, deep interview and focus group discussion activities, which being process with Analytical Hierarchy Process (AHP) with helping by expert choice. Based on AHP result, the priority of stakeholders perceptions on marine tourism management of Kapoposan Islands in Pangkep Regency as like this follow: the Central Goverment, the Regency Goverment, the private sector, and non bureaucracy institusion